2021
DOI: 10.3390/su132312981
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Choline Chloride-Based Natural Deep Eutectic Solvents (NaDES) and Their Applicability for Extracting Oil Palm Flavonoids

Abstract: Oil palm (Elaeis guineensis Jacq.) leaf (OPL) is abundantly generated from oil palm plantations as biomass that is rich in bioactive metabolites, primarily flavonoids. Six natural deep eutectic solvents (NaDES) were synthesized using a direct heating technique from different combinations of choline chloride with 1,2-propanediol (PD), 1,4-butanediol (BD), glycerol (GLY), glucose (GLU), maltose (MAL) and lactic acid (LA). The synthesized NaDES were subjected to physicochemical and biological evaluations comprisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Choline chloride (ChCl) was the first HBA used in DESs and the one present in over half of the DESs reported in the literature. , The distinctive character of ChCl in forming DESs with a considerably low eutectic temperature has not been well-explored so far. ChCl has been shown to undergo a solid–solid transition at around 352 K .…”
Section: Introductionmentioning
confidence: 99%
“…Choline chloride (ChCl) was the first HBA used in DESs and the one present in over half of the DESs reported in the literature. , The distinctive character of ChCl in forming DESs with a considerably low eutectic temperature has not been well-explored so far. ChCl has been shown to undergo a solid–solid transition at around 352 K .…”
Section: Introductionmentioning
confidence: 99%
“…The rise of polarity in DES indicates higher hydrogen bond forming tendency, and therefore, it can deduce that organic acid‐based NADES (acidic HDB) has a higher hydrogen bond forming ability and produces highly polar DES. Comparative to sugar‐based NADES, the polarity of BDO‐ and EG‐based DES is still high, which highlights a great potential in solubility and extraction of anthocyanin in DES 21 …”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the simple structure of LA with only one −COOH group aided a better interaction for extraction. Furthermore, previous research work also revealed that organic acid‐based NADES is more polar than polyalcohol‐based DES, making the organic acid‐based NADES with high anthocyanin extraction efficiency 21,22 . Unlike complex polyalcohol HBD such as sorbitol and polyethylene glycol, EG and BDO defined as simple polyalcohol HBD in which the viscosity of these DES is lower compared to sorbitol and polyethylene as HBD 24 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations